Kualitas Air Sungai - Desi Nursaini; Arman Harahap (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to analyze the water quality of the Barumun river in Pinang City based on water quality criteria and formulate a pollution control strategy that needs to be implemented. The method used is descriptive and quantitative by analyzing river water quality status based on the pollution index. The results showed that the PI value of Barumun river water ranged from 0.82 to 1.71. The recommended pollution control strategies are: 1) maintaining river border protection zones involving environmental cadres and green communities in monitoring; 2) supervision and control of water pollution along the river; 3) improving monitoring of river water quality and supervision of wastewater discharge into rivers; 4) the granting of a wastewater disposal permit (IPLC) to the river must pay attention to the condition of the capacity of the river's pollution load capacity and enforce environmental laws against business actors who violate the established environmental quality standards. In conclusion, the Barumun River in Kota Pinang has decreased in quality, with the status of water quality being lightly polluted. The recommendations for water pollution control strategies that need to be implemented are progressive strategies. Keywords: Water Quality, Water Pollution Control, Water Quality Status